Doping Mechanism of Ge4+ Ions in Ge4+‐Doped TiO2. Issue 4 (20th November 2017) - Han, Zhongxing; Yu, Yanlong; Cao, Yaan
Abstract : A series of Ge 4+ ‐doped TiO2 is synthesized by a sol–gel method and annealed at different temperatures. The doping mechanism of Ge was studied via XRD, Raman spectroscopy, XPS, and HRTEM techniques. The doping behavior of introduced Ge 4+ ions is related to the doping concentration and annealing temperature. It is revealed that the Ge 4+ ions would exist as doped Ge ions in substitutional mode and GeO2 on surface. At certain concentration, the substitutional‐doped Ge ions are transferred to GeO2 on surface with the increase of annealing temperature. The introduction of Ge 4+ ions inhibited the formation of the rutile phase of TiO2 and delayed the phase transition. Abstract : Han et al. study the doping mechanism in germanium‐doped titania samples. The Ge 4+ ions can be doped into the TiO2 lattice in substitutional mode at a concentration smaller than saturation, whereas excess ions form GeO2 on the surface. With increasing temperature, the substitutionally doped Ge ions are transferred to GeO2 on the surface. The substitutional Ge 4+ ions in the lattice can inhibit conversion from anatase TiO2 to rutile TiO2, leading to an increase of the phase‐transition temperature.